How does climate exacerbate root causes of conflict in Sudan? An econometric analysis - Kangogo, Daniel; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Sudan, using a two-stage econometric approach. The findings show that food insecurity is the mechanism through which climate change influences conflict. In other words, climate change indirectly exacerbates conflict by adversely affecting food security.